(untitled) (Research, Society and Development, 2021)
The airport is essential for air transport, mainly because it is and place where the transfer of air and land transport modes takes place and, vice versa. In the case of Santarém airport, it is also important to stress its strategic position in the Amazon, as it is geographically located between the Manaus and Belém axis, which concentrate the largest operations in the region. In this way, the present work intends to verify the vertical light signaling infrastructure of Santarém Airport, comparing it with the normative requirements, as well as to describe a sequence of methodological procedures to be referenced in the elaboration of a regional airport project. With the data, it was possible to propose a vertical light signaling system with high energy efficiency, guaranteeing operational safety and complying with current regulations. Thus, the characteristics of the mandatory instruction, information, location and destination panels, power transformers, shelters for transformers, and their connections were defined.